Decision making style and investment success of retail investors in Malaysia - Amer Azlan Abdul Jamal; Wijaya Kamal Ramlan; Khairul Hanim Pazim; Dayang Safrina Ag Budin (Center for Promoting Ideas (CPI), USA, 2014)
Since the past three decades, numerous contributions have been made by the traditional finance proponents in assisting investors making good investment decisions assuming that they are rational decision makers, and unbiased in predicting the future. Nevertheless, proponents of behavioural finance always argued that people do act in irrational manner and often make predictable errors in their forecasts thus violated these assumptions. Market anomalies and crashes are some of the examples that explain the existence of psychological bias that lead to inefficient outcomes. When come to investing, different investors would have different investment style and strategy, depending on their objectives. Some don’t even have strategy and would rather ask for ‘hot tips’ or listening to rumours. Prior studies revealed that some investors would prefer listening to strangers when the stock is fundamentally strong and consistent with their investment goals. This consequently would affect their investment objectives, causes mispricing, discourage trading among market participants and contribute towards market inefficiencies. Thus, in line to address this gap, the main objective of this research is to study the factors that influence investors’ decision-making style and investment success. The research framework is adopted from Muhammad and Abdullah (2009), which suggested that investors’ decision-making style and investment success could be influenced by the ability to analyze the environmental, financial and economic information (i.e rational manner) and individuals’ emotions and frame of references (irrational manner). The research identified that investors’ decision-making style is heavily influenced by financial analysis in which contributes towards their investment decision success. In other words, investors are rational when making decision investing in the capital market. On the other hand, other variables do not show any significant relationship with the dependant variable.